Studying Bankruptcy of Companies Falling into the Liquidity Trap in Tehran Stock Exchange - Hajipoor, Meysam (2020)
Improper working capital policies may put companies in a situation where they may have difficulty securing their cash resources; in the financial sector, this is called a liquidity trap. The liquidity trap implies the inability of companies to provide cash resources due to inappropriate working capital policies. Theoretically speaking, companies falling into the liquidity trap have difficulty in fulfilling their obligations and paying off debts, due to applying proper liquidity policies; resulting from lack of cash flows or cash outflows, due to the internal or external factors, they are subject to financial limitations and ultimately bankruptcy. The purpose of this study is to investigate whether the companies listed in the Tehran Stock Exchange that have been fallen in the liquidity trap, eventually go bankrupt; using the data of 206 companies in the period of 2008-2017 and based on the liquidity trap prediction model of Vakili Fard et al., the financial limitation prediction models of Kaplan and Zingales, Witedo and modified Kaplan and Zingales, as well as modified Altman bankruptcy prediction models and genetic algorithm, we examined this hypothesis. Confirming the research hypothesis, it was concluded that companies with liquidity trap go bankrupt, unless they reform or change their working capital policies.